(untitled) (Nigerian Journal of Technology, 2014)
This paper describes a new power conversion circuit topology for single-phase DC-AC boost converter, based on the dc-dc boost converter. It comprises an H-bridge, fed from a single input dc source through a boosting inductor. Change of load current flow is achieved with four current-steering diodes. The proposed boost inverter configuration performs single stage power conversion, which minimizes switching losses and attains higher efficiency as compared to the conventional boost inverter. The steady-state operating principle of the power circuit configuration and control strategy are described. A multi-loop structure controller is used to ensure a high dynamic performance. Computer simulations demonstrate the feasibility of the proposed boost inverter. http://dx.doi.org/10.4314/njt.v33i2.14